2014
DOI: 10.1016/j.biortech.2014.06.090
|View full text |Cite
|
Sign up to set email alerts
|

Combining microbial cultures for efficient production of electricity from butyrate in a microbial electrochemical cell

Abstract: Butyrate is an important product of anaerobic fermentation; however, it is not directly used by characterized strains of the highly efficient anode respiring bacteria (ARB) Geobacter sulfurreducens in microbial electrochemical cells. By combining a butyrate-oxidizing community with a Geobacter rich culture, we generated a microbial community which outperformed many naturally derived communities found in the literature for current production from butyrate and rivaled the highest performing natural cultures in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…4b) decrease from interface to the anode surface. Moreover, as it has been proved by experiments [45,46] the major biofilm microorganisms are electrogens and for this simulation the mean value of electrogens to methanogens ratio is 5.94. The biofilm thickness varied dynamically from 11 micron to 14.6 micron over time (Fig.…”
Section: Evaluation Of the Model Mfc-related Partmentioning
confidence: 98%
“…4b) decrease from interface to the anode surface. Moreover, as it has been proved by experiments [45,46] the major biofilm microorganisms are electrogens and for this simulation the mean value of electrogens to methanogens ratio is 5.94. The biofilm thickness varied dynamically from 11 micron to 14.6 micron over time (Fig.…”
Section: Evaluation Of the Model Mfc-related Partmentioning
confidence: 98%
“…The oxidation of acetate by the electrogenic bacteria and endogenous respiration processes are the main sources of electron generation. Thus, the electron mass balance is defined as follows [13]: (24) where , are determinations of electrons generated by substrate consumption (molekgCODS -1 ) and self-oxidation of biomass through endogenous respiration (mole-kgCODX -1 ), and show the fraction of energy-generating electrons (dimensionless) and time conversion factor (86400 s day -1 ), respectively.…”
Section: Electron Mass Balance Equationmentioning
confidence: 99%
“…These microbial groups are therefore in A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 5 competition with one another. Due to the assumption that electrons are transferred by the conduction-based mechanism, not mediated transfer, electrogens are considered existent in the biofilm [24,25]. The degradation rate of organic wastewater, and rate of acetate consumption by acetoclastic methanogenic bacteria in the liquid bulk are represented as follows [21]: …”
Section: Kinetic Rate Equationsmentioning
confidence: 99%
“…Syntrophic microbial consortia are widely used in microbial fuel cells, where multiple fermentative bacteria degrade a mixture of complex organic pollutants and exoelectrogenic microorganisms (typically Geobacter species) rapidly convert fermentation intermediates into electrical current or chemicals/biofuels thereby eliminating their feedback inhibition on fermentative bacteria 106 . Synthetic microbial consortia have been used to design more efficient microbial fuel cells 107; 108; 109; 110; 111; 112; 113 . A notable example is the study by Venkataraman et al 110 , which demonstrated that a mutualistic co-culture of Pseudomonas aeruginosa and Enterobacter aerogenes in a bioelectrochemical system leads to up to 14-fold increase in electric power generation compared to either of the monocultures.…”
Section: Applications Of Synthetic Ecology In Biomedicine Metabolic mentioning
confidence: 99%
“…A more recent study addressed the issue that butyrate, which is an anaerobic fermentation by-product is not directly used by Geobacter sulfurreducens in anode. A synthetic consortium composed of two different but complementary mixed cultures was designed for the anode to overcome this issue, where one oxidizes butyrate to acetate and the other (enriched in Geobacter species) produces electric current by the consumption of acetate 112 . This synthetic community led to an enhanced production of electric current that outperformed the previous naturally derived communities.…”
Section: Applications Of Synthetic Ecology In Biomedicine Metabolic mentioning
confidence: 99%